Pengaruh Waktu Penahanan Artificial Aging Terhadap Sifat Mekanis dan Struktur Mikro Coran Paduan Al-7%Si - Subowo Subowo; Hari Subiyanto (Institut Teknologi Bandung, 2002)
Holding time conducted at specified temperature determines precipitation hardening and affect mechanical properties of Al-Si alloy. The duration of holding time produces different mechanical properties, and this research examines the most suitable holding time to produce the best mechanical properties. In this research, the experiment is done using Al-Si Alloy with heat solution treatment at 520 0C, and then further quenched to artificial aging temperature of 154 0C with holding time 1, 3, 5, 7 hours. This result will be compared to Al-Si Alloy one day quenched at temperature of 30 0C without artificial aging. After the experiment, tensile test, hardness test and micro structural test were conducted. The experiment results show that increasing holding time from 5 hours until 7 hours enhances strength of material test drastically but its strain decreases.